Deformable and flexible electrospun nanofiber-supported cross-linked gel polymer electrolyte membranes for high safety lithium-ion batteries. Issue 37 (25th April 2017) - Tong, Yongfen; Xu, Yuzhong; Chen, Dian; Xie, Yu; Chen, Lie; Que, Mingming; Hou, Yang
Abstract : A deformable and flexible Li/CGPE/LiFePO4 cell based on CGPE-3 exhibited a high specific capacity and superior cycling stability for lithium-ion batteries. Abstract : A deformable and flexible cross-linked composite gel polymer electrolyte (CGPE) membrane, blended with an ionic liquid (IL) diluent, was successfully prepared for lithium-ion batteries. Herein, a cross-linked composite gel polymer electrolyte membrane in the presence of an IL resulted in the formation of a solid-like, elastic gel directly within the poly(vinylidene fluoride- co -hexafluoropropylene) electrospun skeleton via in situ UV-induced cross-linking of poly(ethylene glycol)methyl ether methacrylate (PEGMA), pentaerythritol tetraacrylate, and PEGMA monomers. The CGPE membrane exhibited significantly improved film flexibility and prevented liquid leakage while maintaining some advantageous features such as good liquid retention, high ionic conductivity, and good thermal stability. Moreover, the CGPE-3 exhibited the best performance, with a wide electrochemical potential window of up to 5.0 V vs. Li + /Li and a high ionic conductivity of 1.7 × 10 −3 S cm −1 . The Li/CGPE/LiFePO4 cells with CGPE-3 exhibited stable electrochemical performance and yielded specific capacities of 160, 150, 136, 122, and 91 mA h g −1 at 0.1, 0.2, 0.5, 1.0, and 2.0C rates, respectively; moreover, they retained their properties well after 100 cycles for each rate. These solid-like gel polymer electrolyte membranes with excellent properties represent a very promising material for high-performance lithium-ion batteries with improved safety and reliability.